(untitled) (Clinics, 2012)
Pancreatico-duodenal tumors are the second most common endocrinopathy in multiple endocrine neoplasia syndrome type 1, and have a pronounced effect on life expectancy as the principal cause of disease-related death. Previous discussions about surgical management have focused mainly on syndromes of hormone excess and, in particular, the management of multiple endocrine neoplasia syndrome type 1-related Zollinger-Ellison syndrome. Since hormonal syndromes tend to occur late and indicate the presence of metastases, screening with biochemical markers and endoscopic ultrasound is recommended for early detection of pancreatico-duodenal tumors, and with early surgery before metastases have developed. Surgery is recommended in patients with or without hormonal syndromes in the absence of disseminated liver metastases. The suggested operation includes distal 80% subtotal pancreatic resection together with enucleation of tumors in the head of the pancreas, and in cases with Zollinger-Ellison syndrome, excision of duodenal gastrinomas together with clearance of regional lymph node metastases. This strategy, with early and aggressive surgery before metastases have developed, is believed to reduce the risks for tumor recurrence and malignant progression.